2021
DOI: 10.20849/jed.v5i1.848
|View full text |Cite
|
Sign up to set email alerts
|

Global Higher Education: Examining Response to the COVID-19 Pandemic Using Agility and Adaptability

Abstract: Global higher education institutions are significantly impacted by a key component of chaos during challenging times: the ability to effectively respond to ambiguity and uncertainty. Today’s COVID-19 global pandemic created a challenge so quickly that higher education leaders had little opportunity to assess, evaluate and make informed judgments. The dynamics of the situation presented more complexities than ever previously faced. Global higher education institutions with the ability to manage ambiguity and un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 34 publications
0
12
0
Order By: Relevance
“…The continuing pandemic will force colleges and universities around the world grapple with student academic learning issues. With the uncertainty abut how "normal" college life will be for all stakeholders in Fall 2021 (McCormack et al, 2021), continued study of these teaching-related issues, including student perceptions, remains important. Given the global experience of universities stuggling with the ongoing pandemic's impact (Tam et al, 2021;Watermeyer, Crick, Knight, & Goodall, 2021), an international collaborative effort among researchers comparing the same student perception variables across different college settings, e.g., United States versus other countries, state-supported versus private, urban versus rural campus location, business versus non-business school, and full-time versus part-time undergraduates, would be ideal for future research.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The continuing pandemic will force colleges and universities around the world grapple with student academic learning issues. With the uncertainty abut how "normal" college life will be for all stakeholders in Fall 2021 (McCormack et al, 2021), continued study of these teaching-related issues, including student perceptions, remains important. Given the global experience of universities stuggling with the ongoing pandemic's impact (Tam et al, 2021;Watermeyer, Crick, Knight, & Goodall, 2021), an international collaborative effort among researchers comparing the same student perception variables across different college settings, e.g., United States versus other countries, state-supported versus private, urban versus rural campus location, business versus non-business school, and full-time versus part-time undergraduates, would be ideal for future research.…”
Section: Discussionmentioning
confidence: 99%
“…For example, COVID-19 forced the closure of seveal colleges in Nigeria (Chinwana, Chinawa, Ossai, Aronu, & Onukwuli, 2021). Much uncertainty remains for many universities and colleges around the world about how "normal" college campus life will be for returning students, faculty and staff in the Fall 2021 (McCormack, Lemoine, Waller, & Richardson, 2021). Recent research on college students in the early pandemic stage found more experienced panic with higher COVID-19 fears and elevated depressive mood (Hasratian, Nordberg, Meuret, & Riz, 2021;Konstantopoulou & Raikou, 2020), as well as the need for modifable prevention intervention strategies to appreciate student perceived barriers and self-efficacy (Tam, Li, Li, Wang, & Lin, 2021).…”
Section: Introduce the Problemmentioning
confidence: 99%
See 1 more Smart Citation
“…The challenges presented to both instructors and students during the evolving COVID-19 pandemic have truly challenged the ways in which pedagogy is used to regain, sustain, and engage students' attention, given the inherent challenges associated with remote learning (Eadens and Eadens, 2021;Gelles et al, 2021;Lysenko and Tokareva, 2021;Mamun et al, 2021;McCormak et al, 2021;O'Sullivan et al, 2021). This has placed an enormous amount of pressure on instructors to find novel, unique, and creative ways to engage their students to maintain their interests and academic momentum from prior to COVID-19 until the situation becomes resolved.…”
Section: Unique Teaching Approaches During and Post Covid-19: 180°video Vr Hmd And 3d Video Computer Display Pedagogy Solutions To Upskilmentioning
confidence: 99%
“…Managing this return-to-college ambiguity is critical. Highlighting the need for agility and adaptability McCormack et al (2021) made several general recommendations, including the need for global higher education institutions to: focus on long-range planning over crisis management, and increase awareness/monitoring of learning design quality.…”
Section: Introduce the Problemmentioning
confidence: 99%